2017
DOI: 10.1073/pnas.1616892114
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicle glycoprotein 2C (SV2C) modulates dopamine release and is disrupted in Parkinson disease

Abstract: SignificanceHere we describe a role for the synaptic vesicle glycoprotein 2C (SV2C) in dopamine neurotransmission and Parkinson disease (PD). SV2C is expressed on the vesicles of dopamine-producing neurons, and genetic deletion of SV2C causes a reduction in synaptic release of dopamine. The reduced dopamine release is associated with a decrease in motor activity. SV2C is suspected of mediating the neuroprotective effects of nicotine, and we show an ablated neurochemical response to nicotine in SV2C-knockout mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(140 citation statements)
references
References 64 publications
2
138
0
Order By: Relevance
“…It is also important to note that [ 11 C]UCB‐J has previously been found to be specific for SV2A and not for SV2B or SV2C . There is preclinical evidence of SV2C disruption in PD pathogenesis . It is possible that SV2C is selectively expressed in dopamine neurons and therefore a more sensitive marker of synaptic loss in the striatum, which would make an SV2C‐specific PET tracer potentially valuable in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that [ 11 C]UCB‐J has previously been found to be specific for SV2A and not for SV2B or SV2C . There is preclinical evidence of SV2C disruption in PD pathogenesis . It is possible that SV2C is selectively expressed in dopamine neurons and therefore a more sensitive marker of synaptic loss in the striatum, which would make an SV2C‐specific PET tracer potentially valuable in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic vesicle PG-2 SV2 occurs as three isoforms, SV2A, SV2B, and SV2C which display variable cellular distributions. These bind the neurotransmitters glutamate, GABA, dopamine, choline, and ATP and also interact with Ach and synaptotagmin (Bartholome et al 2017;Dunn et al 2017). SV2 forms a smart gel storage matrix within synaptic vesicles (Reigada et al 2003).…”
Section: Sulfation Of Ks Glycoforms On Pgs and Its Impact On Neuroregmentioning
confidence: 99%
“…At the time of this GWAS finding, little was known about SV2C except that it was highly expressed in the substantia nigra and that it might be involved in dopamine release. The discovery of SV2C in GWAS prompted functional studies to decipher its role in PD and pharmacogenetic studies to test it as a candidate marker for drug response . Functional studies found that disrupted expression of SV2C is a unique pathological feature of PD; it causes reduced dopamine release in the dorsal striatum, reduced striatal dopamine content, disrupted α‐synuclein expression, abnormal motor function in rodents, and alterations in neurochemical effects of nicotine .…”
Section: Precision Medicine and Pharmacogenomicsmentioning
confidence: 99%
“…The discovery of SV2C in GWAS prompted functional studies to decipher its role in PD and pharmacogenetic studies to test it as a candidate marker for drug response . Functional studies found that disrupted expression of SV2C is a unique pathological feature of PD; it causes reduced dopamine release in the dorsal striatum, reduced striatal dopamine content, disrupted α‐synuclein expression, abnormal motor function in rodents, and alterations in neurochemical effects of nicotine . A clinical study examined SV2C and other biological variables as potential markers for l ‐dopa dose response and adverse effects .…”
Section: Precision Medicine and Pharmacogenomicsmentioning
confidence: 99%
See 1 more Smart Citation